2023
DOI: 10.1088/2632-2153/acefa9
|View full text |Cite
|
Sign up to set email alerts
|

New angles on fast calorimeter shower simulation

Sascha Diefenbacher,
Engin Eren,
Frank Gaede
et al.

Abstract: The demands placed on computational resources by the simulation requirements of high energy physics experiments motivate the development of novel simulation tools. Machine learning based generative models offer a solution that is both fast and accurate. In this work we extend the Bounded Information Bottleneck Autoencoder (BIB-AE) architecture, designed for the simulation of particle showers in highly granular calorimeters, in two key directions. First, we generalise the model to a multi-parameter conditioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Unlike previous image-based fast simulation models such as ref. [16,18,21], the computational cost of the PointWise Net scales O (𝑁) with the number of points and hence with the energy 𝐸 just like Geant4. Therefore, to improve overall training and sampling speed, we batch together events with a similar number of points.…”
Section: Jinst 18 P11025mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous image-based fast simulation models such as ref. [16,18,21], the computational cost of the PointWise Net scales O (𝑁) with the number of points and hence with the energy 𝐸 just like Geant4. Therefore, to improve overall training and sampling speed, we batch together events with a similar number of points.…”
Section: Jinst 18 P11025mentioning
confidence: 99%
“…The concept of generative calorimeter simulation is well-proven at this point. Its underlying mathematical viability has been demonstrated [4,5] and direct applications have been shown using generative adversarial networks [6][7][8][9][10][11][12][13][14][15], autoencoder-variants [16][17][18], normalizing flows [19][20][21] and diffusion models [22][23][24]. They have been successfully deployed e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The application of deep generative models to calorimeter simulation began with CaloGAN [1,2]. Since that time, Generative Adversarial Networks (GANs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], Variational Autoencoders [15,16,[18][19][20][21], Normalizing Flows (NFs) [22][23][24][25][26][27][28][29], and Diffusion Models [30][31][32][33] have been applied to this problem. This research entered a precision era with the first NF application (CaloFlow) [23], which showed that even a post-hoc classifier had difficulty distinguishing physics from machine learning simulators.…”
Section: Introductionmentioning
confidence: 99%
“…Detector simulations, such as the simulation of the sensor response in highly granular calorimeters, can be augmented or sped up by employing modern generative machine learning methods [5][6][7][8]. Recent studies have explored the simulation of calorimeter showers with various generative models such as generative adversarial networks (GANs) [5,[9][10][11][12][13][14][15][16][17][18][19], autoencoders and their variants [20][21][22][23][24][25], and normalizing flows [26][27][28][29][30][31][32][33]. Additionally, diffusion models [34][35][36][37][38], also referred to as score-based generative models, have been shown to provide very high fidelity on calorimeter data [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%